Rehabilitasi Mangrove sebagai Upaya Mitigasi terhadap Abrasi Pantai Puuk, Aceh Utara - Ruzanna, Arina; Syahrial Syahrial; Latifah Latifah; Suhartin Suhartin; Ananta Wira (Lembaga Pengembangan Kinerja Dosen, 2025)
Puuk Beach is one of the beaches located in North Aceh. This beach is used as a tourist spot, transportation and fishing area. In this Community Service activity, mangrove rehabilitation was carried out on Puuk beach with the aim of providing important information related to preserving the mangrove ecosystem as an effort to mitigate coastal abrasion. This activity involves the community around Puuk Village. The method used in this community service is education by providing mangrove-related material and coupled with direct mangrove planting in the area. In general, this activity ran smoothly and was followed with quite high enthusiasm by all participants.It is hoped that with this activity addition, the mangrove forest ecosystem can be the location of fishing and recreational tourism so that it can increase the amount of income of the Puuk Village community in the future.